2014
DOI: 10.1007/s00704-014-1299-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Rwandan seasonal rainfall anomalies and ENSO events

Abstract: This study aims primarily at investigating the relationships between Rwandan seasonal rainfall anomalies and El Niño-South Oscillation phenomenon (ENSO) events. The study is useful for early warning of negative effects associated with extreme rainfall anomalies across the country. It covers the period 1935-1992, using long and short rains data from 28 weather stations in Rwanda and ENSO events resourced from Glantz (2001). The mean standardized anomaly indices were calculated to investigate their associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
(90 reference statements)
1
21
0
Order By: Relevance
“…For Rwanda specifically, one study of historical station rain gauge data (up to the early 1990s) found that a little over 40% of the annual rainfall occurred in the March-May season, between 30 and 40% occurred in the September-December season, and about 15-20% occurred in January and February with June-August typically having only about 5% of the annual rain (Muhire et al, 2015). One study found that the pluviometric coefficient (ratio of monthly rainfall to annual rainfall) is more spatially heterogeneous across the country in February and October than in other months, potentially suggesting a role of additional sources of moisture (e.g., advection from the Congo and/or Atlantic).…”
Section: Rainfall Climatologymentioning
confidence: 99%
See 4 more Smart Citations
“…For Rwanda specifically, one study of historical station rain gauge data (up to the early 1990s) found that a little over 40% of the annual rainfall occurred in the March-May season, between 30 and 40% occurred in the September-December season, and about 15-20% occurred in January and February with June-August typically having only about 5% of the annual rain (Muhire et al, 2015). One study found that the pluviometric coefficient (ratio of monthly rainfall to annual rainfall) is more spatially heterogeneous across the country in February and October than in other months, potentially suggesting a role of additional sources of moisture (e.g., advection from the Congo and/or Atlantic).…”
Section: Rainfall Climatologymentioning
confidence: 99%
“…There has been regional hydro-climatic variability on multi-decadal timescales (Ilunga and Muhire, 2010;Mbungu et al, 2012;Muhire et al, 2015;Muhire and Ahmed, 2015a). On shorter, inter-annual timescales, the El Nino-Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) play a significant role in the rainfall patterns of Rwanda in particular and East Africa more generally (Ropelewski and Halpert, 1987;Saji and Yamagata, 2003;Ilunga and Muhire, 2010;Muhire et al, 2015;Ndomeni et al, 2018).…”
Section: Rainfall Climatologymentioning
confidence: 99%
See 3 more Smart Citations